Специфіка мовної лояльності на пострадянському просторі (приклад Молдови) - Яворська, Г.М. (Мовознавство, 2013)
У статті розглянуто характеристики мовної лояльності та її специфіку на пострадянському просторі. Встановлено зв’язок мовної лояльності з особливостями мовної ситуації та мовними ідеологіями. За допомогою результатів аналізу фокус-груп показано дискурсивні вияви мовної лояльності в Молдові. Визначено вплив фактора «першої мови» на види мовної лояльності. The regular language conflicts in post-Soviet states calls attention to the language loyalties in these countries. The peculiarity of language loyalties here is a result of language situations determining by the specific type of asymmetrical bilingualism receiving from the Soviet period. Attitude towards Russian is of crucial importance for speakers whether it is the first language or the second one. The case of Moldova is significant as it reveals specific features of some post-Soviet language ideologies and their impact on manifestation of language loyalty. This article examines the data collected during the field research in Moldova in 2010. The focus groups methodology enables to explore the discursive dimension of language loyalty. It helps to reveal people’s views of languages they use so as their covert language attitudes that shape different language loyalty models. The researchers concentrated on the situations of communicative conflicts connected with the Romanian — Russian bilingualism. It concerns the unwillingness and/or impossibility of use Romanian / Moldavian or Russian in everyday communication. Focus group participants use different narrative strategies depending of their first language. The participants with Russian as L! are inclined to believe that the interlocutor intentionally does not want to speak their language pretending to be ignorant. Hence, they think an interlocutor is a liar. Whereas the participants with Romanian as L, consider similar cases as overt lack of respect for official language. The lack of language loyalty they understand as aggression. Thus, the Lj factor determines the model of language loyalty. The speakers incline to identify themselves with their first language (native tongue) which they informally call normal.